Assessment and outcomes of firefighter applicants with possible asthma. (17th December 2021) - Kabir, T; Schofield, S; Fitzgerald, B; Cannon, J; Szram, J; Feary, J
Abstract: Background: Firefighter applicants (FFAs) with a history of asthma may be refused entry to the fire service because of potentially putting themselves and others at risk. Aims: We undertook a service evaluation to identify respiratory and employment outcomes of FFAs with a history of asthma who had undergone additional respiratory assessment at our specialist occupational lung disease clinic during 2005–19. Methods: We reviewed FFA medical records and categorized them as having either no current asthma or definite/probable asthma at the time of clinic assessment. 'No current asthma' was defined as negative non-specific bronchial hyper-responsiveness (BHR) to histamine/methacholine, and no symptoms or treatment within the 2 years before clinic. 'Definite/probable current asthma' was defined as either positive BHR, or negative BHR with symptoms and/or treatment within the previous 2 years. Around 1 year later, we contacted FFAs to enquire about their application outcome and current respiratory symptoms. Results: Data were available on 116 applicants; of whom, 45% ( n = 52) had definite/probable current asthma and were significantly more likely to be older, atopic to common aeroallergens, report atopic disease and have a lower forced expiratory volume in one second/forced vital capacity ratio compared with applicants with no current asthma. Only two individuals' applications were rejected due to asthma. At follow-up, just 2 (2%) of the 90 operational firefighters reported any recent trouble with asthma. Conclusions: A history of asthma alone is not sufficient to determine current asthma in FFAs. Even with a diagnosis of current asthma, FFAs are mostly successful in their application to join the fire service.